2001
DOI: 10.2169/internalmedicine.40.292
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Recurrence in 36 Subacute Thyroiditis Patients Managed with Prednisolone.

Abstract: Objective The incidence of subacute thyroiditis (SAT) is lowand there are a fewreports of recurrence of subacute thyroiditis. Current treatment protocols for SATare not uniform. Prednisolone (PSL) is chosen more often for treatment than nonsteroidal anti-inflammatory drugs. This study was undertaken to confirm the recurrence rate of SAT managed by PSL, and to compare the initial laboratory data between the recurrent and the non-recurrent groups. Methods After diagnosis, all patients were treated with PSL (star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
52
0
5

Year Published

2002
2002
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(72 citation statements)
references
References 15 publications
15
52
0
5
Order By: Relevance
“…The recurrence rate of 15.2% noted in the present study was similar to that reported in previous studies (ranging from 10 to 20%) [3,9]. Mizukoshi et al [9] noted that the breaking point for recurrence may occur at a 10 mg PSL dose, and suggested that extending the period under treatment with 10 mg PSL may help reduce the recurrence rate [9]. In our study, recurrence was also observed when the PSL dose was tapered from 10 to 5 mg/day, which was in agreement with the above results reported by Mizukoshi et al [9].…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…The recurrence rate of 15.2% noted in the present study was similar to that reported in previous studies (ranging from 10 to 20%) [3,9]. Mizukoshi et al [9] noted that the breaking point for recurrence may occur at a 10 mg PSL dose, and suggested that extending the period under treatment with 10 mg PSL may help reduce the recurrence rate [9]. In our study, recurrence was also observed when the PSL dose was tapered from 10 to 5 mg/day, which was in agreement with the above results reported by Mizukoshi et al [9].…”
Section: Discussionsupporting
confidence: 92%
“…These results point to similarities of the phenotype in the two studies, though with slightly lower rates of these two features of SAT in our group of patients. The recurrence rate of 15.2% noted in the present study was similar to that reported in previous studies (ranging from 10 to 20%) [3,9]. Mizukoshi et al [9] noted that the breaking point for recurrence may occur at a 10 mg PSL dose, and suggested that extending the period under treatment with 10 mg PSL may help reduce the recurrence rate [9].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations